2000
DOI: 10.1089/027245700429828
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlations of α2,6-Sialyltransferase Expression in Colorectal Cancer Patients

Abstract: We have previously demonstrated a link between alpha2,6-Sialyltransferase (alpha2,6-ST; E.C. 2.4.99.1) expression and differentiation of colon tumors. So far, information is not available relative to the expression of alpha2,6-ST in tumors and the survival of patients with colorectal cancer. We have examined the expression of alpha2,6-ST in a variety of colorectal adenocarcinomas (n = 46) at different stages of differentiation (G1 to G3) by immunoperoxidase assay using monoclonal antibody (MAb) 6B9. Clinical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…Some authors reported the higher immunoreactivity of the enzyme a-2,6-sialyltransferase in well differentiated tumors (e.g. in hepatic cell carcinoma [21]), but others found the a-2,6-GalST immunoexpression to be more prevalent in tumors of higher histological grade (colorectal cancer [11], pancreatic cancer cell line [12]). The same concerns the influence of on cellular motility and invasive capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported the higher immunoreactivity of the enzyme a-2,6-sialyltransferase in well differentiated tumors (e.g. in hepatic cell carcinoma [21]), but others found the a-2,6-GalST immunoexpression to be more prevalent in tumors of higher histological grade (colorectal cancer [11], pancreatic cancer cell line [12]). The same concerns the influence of on cellular motility and invasive capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found a-2,6-GalSA to be associated with cell differentiation and proliferation [7], intercellular and cell-matrix interactions [8] and immunity [9]. Their role in cancer has not yet been fully established, although available studies tend to demonstrate it as an indicator of poor prognosis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Columns, mean of four independent experiments done in duplicate; bars, SD. ST6Gal-I expression correlates with a poor prognosis in patients with colorectal and breast cancer (29,30). In vitro cell culture studies suggest that ST6Gal-I up-regulation may contribute to metastasis by regulating invasiveness and/or cell motility (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of ST6Gal-I and α2,6-sialic acid have been observed in various cancer cells and are associated with a poor prognosis in cancer progression [11] . In vitro cell culture studies suggest that ST6Gal-I up-regulation may contribute to metastasis by regulating invasiveness and cell motility.…”
Section: Discussionmentioning
confidence: 99%